Systemic uptake and intestinal inflammatory effects of luminal bacterial cell wall polymers in rats with acute colonic injury. - Sartor, R B (1988)
The systemic uptake and local intestinal inflammatory potential of luminal bacterial cell wall polymers in rats with normal and acutely inflamed colons were measured. Rats were injected intracecally with either 125I-labeled group A streptococcal peptidoglycan-polysaccharide complexes or equal amounts of Na125I, after either nonspecific colonic injury with 4% acetic acid or injection with buffer. The colons of rats injected with peptidoglycan-polysaccharide had higher inflammatory scores than Na125I-injected rats, a greater incidence of mucosal ulceration and transmural inflammation after acetic acid injury, and an increased frequency of focal accumulations of inflammatory cells in the lamina propria and submucosa after buffer injection. Radioactivity in the liver, spleen, and mesenteric lymph nodes was higher in the colon-injured rats that received peptidoglycan-polysaccharide 48 h before tissue collection than in the noninjured rats (P less than 0.002). Group A streptococcal polysaccharide antigen concentration within the liver, spleen, and mesenteric lymph nodes, measured by enzyme-linked immunosorbent assay, was significantly higher in the colon-injured rats that received cell wall polymers than in noninjured rats. These results indicate that luminal bacterial cell wall polymers with well-described inflammatory and immunoregulatory potential can cross injured colonic epithelia and are capable of initiating and potentiating intestinal inflammation.